TEMPE FORMULATION AS COMPLEMENTARY FOODS FOR BREAST MILK TO MEET THE NUTRITIONAL NEEDS OF BABIES? COMPLEMENTARY FOODS FOR BREAST MILK - Albert Muna; Nurdin Beta; Rasniah Sarumi; Elna Sari (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: Complementary food for breast milk is food or drink that contains nutrients, given to babies or children aged 6-24 months to meet nutritional needs other than breast milk. Complementary Foods which functions to introduce babies from breast milk to family food. The aim of this research is to determine the effectiveness of tempe formulations as Complementary Food for Breast Milk in meeting the nutritional needs of babies. Methods: The research method used is quantitative using an experimental design namely one of the pre-experimental methods where there is no comparison group (control) but a first observation has been carried out (pretest which tests changes after treatment). The population in this study were babies 6-12 months who had a low BMI as many as 43 babies. The sampling technique uses saturated sampling, namely all the population is sampled. Results: The results of the research show that respondents who consume tempeh as complementary breast milk can meet the nutritional needs of babies which can be seen from the changes in baby's weight which increase every month. Conclusion: It was concluded that the tempeh formulation could increase the nutritional needs of babies.